Business cycles and monetary regimes in emerging economies: A role for a monopolistic banking sector - Federico S. Mandelman (Federal Reserve Bank of Atlanta, 2009)
This study shows that the presence of imperfect competition in the banking system propagates external shocks and amplifies the business cycle. Strategic limit pricing, aimed at protecting retail niches from potential competitors, generates countercyclical bank markups. Markup increments during recessions directly increase borrowing costs for firms and indirectly damage the financial position of firms' balance sheets, increasing lenders' risk perception. I use Bayesian techniques and data from Argentina to show that the inclusion of monopolistic banking improves the fit of the New Keynesian small open economy model.
Keywords: E32; F41; G15; G21; L12; 330; small open economy; countercylical bank markups; exchange rate regimes; Bayesian estimation; balance sheet effect